Steven Freidman, Power in Action: Democracy, Citizenship and Social Justice. Johannesburg: Wits University Press, 2018, 271pp. (The Strategic Review for Southern Africa, 2020)
Professor Steven Freidman’s book on the challenges facing South Africa’s democracy comes at a time when the Electoral Commission of South Africa (IEC) just hosted the highly contested national elections since 1994. Again, the book comes at a period where cut-throat power struggle politics of coalition governments at local government level are at their peak. The momentum and growth of opposition parties after 25 years of democracy in South Africa signal the growth and maturing of the ‘Rainbow Nation’ democracy. Opposition parties such as the Economic Freedom Fighters (EFF) are in an expedition to influence the African National Congress (ANC) led government to amend or review the South African Constitution of 1996; aimed at addressing the triple-headed monster (unemployment, income inequality and poverty). This book is also released at a time when troubled African states such as Sudan and Zimbabwe had undergone coup d’état and violent national protests over democracy upliftment. This premise rightly coincides with Freidman’s contention that authoritative leaders particularly in Africa deploy democracy to win elections but they are unable to ostensibly operate within democratic norms (pp vii-ix). This reflection can be well aligned to the assertion of Kenyan public intellectual, legal expert and scholar, Professor Patrick Lumumba “democracy is a competition of ideas, sustained by the constant dialogue where the minority have their say and the majority have their way.”